Changes in tidal dynamics in response to sea level rise in the Sylt-Rømø Bight (Wadden Sea) - Gaziza Konyssova; Vera Sidorenko; Alexey Androsov; Lasse Sander; Sergey Danilov; Sara Rubinetti; Hans Burchard; Christian Winter; Karen Helen Wiltshire (Ocean Dynamics, 2025)
The Wadden Sea is a complex coastal system where sea level rise (SLR), tidal dynamics, and geomorphology interact non-linearly. Today, the functioning of coastal ecosystems and their services in this region, historically resilient to natural changes in sea level, is at risk due to climate change-induced SLR. This study investigates the changes in tidally induced transport pathways of passive tracers, while providing a comprehensive analysis of tidal inundation, asymmetry, and current velocities under different SLR scenarios projected for 2050. The Sylt-Rømø Bight, a semi-enclosed basin, serves as the study site. Using FESOM-C coastal ocean model with a Lagrangian tracking module on a high-resolution unstructured mesh (up to 2 m resolution in the intertidal zone), we simulate tidal dynamics under SLR scenarios based on projections under low (SSP1-2.6) and high (SSP5-8.5) emission scenarios. Results show submerged areas increase by 2–3%, corresponding to a 4–7% loss of intertidal zones by 2050. As the increased depth and inundation affect the system, tidal channels show contrasting changes in current velocities, suggesting shifts in transport pathways. Meanwhile, weakening tidal asymmetry points to a shift toward a more lagoon-like system, leading to a subsequent reduction in outflowing net transport of passive tracers by up to 10%. This study offers insights into tidal transport patterns in the bight, emphasizing the separation between the southwestern and northeastern regions, both in current and future scenarios. It also provides a methodology for analyzing and explaining SLR-induced changes in the dynamics of shallow, tidally dominated areas. The findings underscore the importance of understanding the complex hydrodynamic response to SLR in coastal areas to meaningfully assess its impacts on tidal ecosystems and to develop efficient mitigation strategies for coastal protection.

Dynamical reconstruction of the upper-ocean state in the central Arctic during the winter period of the MOSAiC expedition - Ivan Kuznetsov; Benjamin Rabe; Alexey Androsov; Ying-Chih Fang; Mario Hoppmann; Alejandra Quintanilla-Zurita; Sven Harig; Sandra Tippenhauer; Kirstin Schulz; Volker Mohrholz; Ilker Fer; Vera Fofonova; et al. (Ocean Science, 2024)
This paper presents a methodological tool for dynamic reconstruction of the state of the ocean, based, as an example, on observations from the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) experiment. The data used in this study were collected in the Amundsen Basin between October 2019 and January 2020. Analysing observational data to assess tracer field and upper-ocean dynamics is highly challenging when measurement platforms drift with the ice pack due to continuous drift speed and direction changes. We have equipped the new version of the coastal branch of the global Finite-volumE sea ice–Ocean Model (FESOM-C) with a nudging method. Model nudging was carried out assuming a quasi-steady state. Overall, the model can reproduce the lateral and vertical structure of the temperature, salinity, and density fields, which allows for projecting dynamically consistent features of these fields onto a regular grid. We identify two separate depth ranges of enhanced eddy kinetic energy located around two maxima in buoyancy frequency: the depth of the upper halocline and the depth of the warm (modified) Atlantic Water. Simulations reveal a notable decrease in surface layer salinity and density in the Amundsen Basin towards the north but no significant gradient from east to west. However, we find a mixed-layer deepening from east to west, with a 0.084 m km−1 gradient at 0.6 m km−1 standard deviation, compared to a weak deepening from south to north. The model resolves several stationary eddies in the warm Atlantic Water and provides insights into the associated dynamics. The model output can be used to further analyse the thermohaline structure and related dynamics associated with mesoscale and submesoscale processes in the central Arctic, such as estimates of heat fluxes or mass transport. The developed nudging method can be utilized to incorporate observational data from a diverse set of instruments and for further analysis of data from the MOSAiC expedition.

Non-linear aspects of the tidal dynamics in the Sylt-Rømø Bight, south-eastern North Sea - Vera Fofonova; Alexey Androsov; Lasse Sander; Ivan Kuznetsov; Felipe Amorim; H. Christian Hass; Karen H. Wiltshire (Ocean Science, 2019)
This study is dedicated to the tidal dynamics in the Sylt-Rømø Bight with a focus on the non-linear processes. The FESOM-C model was used as the numerical tool, which works with triangular, rectangular or mixed grids and is equipped with a wetting/drying option. As the model's success at resolving currents largely depends on the quality of the bathymetric data, we have created a new bathymetric map for an area based on recent studies of Lister Deep, Lister Ley, Højer Deep and Rømø Deep. This new bathymetric product made it feasible to work with high-resolution grids (up to 2 m in the wetting/drying zone). As a result, we were able to study the tidal energy transformation and the role of higher harmonics in the domain in detail. For the first time, the tidal ellipses, maximum tidally induced velocities, energy fluxes and residual circulation maps were constructed and analysed for the entire bight. Additionally, tidal asymmetry maps were introduced and constructed. The full analysis was performed on two grids with different structures and showed a convergence of the results as well as fulfilment of the energy balance. A great deal of attention has been paid to the selection of open-boundary conditions, model validation against tide gauges and recent in situ current data. The tidal residual circulation and asymmetric tidal cycles largely define the circulation pattern, transport and accumulation of sediment, and the distribution of bedforms in the bight; therefore, the results presented in the article are necessary and useful benchmarks for further studies in the area, including baroclinic and sediment dynamics investigations.

On the assimilation of absolute geodetic dynamic topography in a global ocean model: impact on the deep ocean state - Alexey Androsov; Lars Nerger; Reiner Schnur; Jens Schröter; Alberta Albertella; Reiner Rummel; Roman Savcenko; Wolfgang Bosch; Sergey Skachko; Sergey Danilov (Journal of Geodesy, 2019)

Impact of wind and tides on the Lena River freshwater plume dynamics in the summer season - Vera Fofonova; Sergey Danilov; Alexey Androsov; Markus Janout; Martin Bauer; Paul Overduin; Polona Itkin; Karen Helen Wiltshire (Ocean Dynamics, 2015)